2010
DOI: 10.1371/journal.pbio.1000347
|View full text |Cite
|
Sign up to set email alerts
|

Need-Based Up-Regulation of Protein Levels in Response to Deletion of Their Duplicate Genes

Abstract: Duplicated genes compensate for loss of one of the paralogs by up-regulating the remaining paralog only under growth conditions in which paralog activity is required for survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
86
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 66 publications
(74 reference statements)
9
86
0
Order By: Relevance
“…Similarly, in agreement with DeLuna et al (27), the model predicts little dosage compensation if we delete a copy of a gene for a gratuitous protein (Fig. 2C).…”
Section: Applicationssupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, in agreement with DeLuna et al (27), the model predicts little dosage compensation if we delete a copy of a gene for a gratuitous protein (Fig. 2C).…”
Section: Applicationssupporting
confidence: 91%
“…We considered whether dosage compensation could arise from the global coupling of gene expression and the negative feedback generated by the trade-offs comprising the model. For example, DeLuna et al (27) examined dosage compensation in over 200 genes in budding yeast and found that increased expression of a paralog upon deletion of its duplicate occurs only for genes required for growth.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…4A) and flow cytometry analysis. LEU9 expression and ␣-IPMS activity were enhanced 3-to 5-fold in a leu4⌬ mutant background, indicating that, as has been previously observed for other paralogous pairs, deletion of one of the paralogs causes the upregulation of its counterpart (36).…”
Section: Leu4⌬ Mutants Accumulate Larger Leucine Pools Than the Wildtsupporting
confidence: 73%